If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) = 4(x + 1) Reorder the terms: 2(-1 + x) = 4(x + 1) (-1 * 2 + x * 2) = 4(x + 1) (-2 + 2x) = 4(x + 1) Reorder the terms: -2 + 2x = 4(1 + x) -2 + 2x = (1 * 4 + x * 4) -2 + 2x = (4 + 4x) Solving -2 + 2x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -2 + 2x + -4x = 4 + 4x + -4x Combine like terms: 2x + -4x = -2x -2 + -2x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -2 + -2x = 4 + 0 -2 + -2x = 4 Add '2' to each side of the equation. -2 + 2 + -2x = 4 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 4 + 2 -2x = 4 + 2 Combine like terms: 4 + 2 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| -13=-2h-7 | | 2*x+3=3*(x-2) | | 4x+7x-9x=2x | | 3(10-5x)=8 | | 5p-2=6p+7 | | -23-4x=7-4x | | 58-6=3x+17 | | 3t-6=9-2t | | 233-7x=29x+21 | | 3.4x+8.7=1.7x+18.9 | | 10x+10=20x+20 | | x^5-x^3+x+1=0 | | 3x+x+2=2x-4 | | 31-9(y+5)=7 | | x^3-96x^2+576x=0 | | -17-9=8x+17 | | 7y-9=33 | | 4x24= | | 5(2x-1)+16=8x+1 | | 3x+1=2x-1 | | -24=6a-15-15a | | 10-10x=75-45x | | 5x-4=-4+5x | | x^4-x^3+1=0 | | 5x=4(x+3) | | 5a-9=26 | | 1=14(2r+1) | | 14-6x=2x+66 | | 8x+29x-6= | | 1.4m-06(m-2)=2.4m | | 2x+40=12x-40 | | 5x-4=2x+6+x |